A Competence-based Approach in Portuguese Early Childhood Education - Isabel Simões Dias; Isabel Kowalski (New Zealand Journal of Teachers' Work)
This paper reports on a Portuguese study in a teacher education context (Polytechnic Institute of Leiria) which, in Portugal, takes place in universities and educational institutes. It aims to reflect on a competence approach in the context of early childhood education. Starting from a concept of competence that considers the subject, action and context, students in the teacher education course (the Degree in Early Childhood Education) made lesson plans (termed, Pedagogic Practice Unit) during the academic year of 2008/2009 in accordance with the Portuguese national guidelines (PT, 1997). These curriculum guidelines do not identify the competences that children should develop. However, the competences identified by students in their lesson plans concerning the curricular areas (area of personal and social education, area of world knowledge, area of expression and communication) were grouped and analysed in relationship to the concept of competences previously assumed. From the data collected, we could infer that it is possible to identify competences to be developed by the children in a kindergarten context and that this identification can be made by the teacher according to the group of children with whom they are working. This research enhances the value of a competence-based approach.